2013
DOI: 10.1111/cdev.12170
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers Selectively Infer History When Explaining Outcomes: Evidence From Explanations of Ownership, Liking, and Use

Abstract: Two experiments provide evidence that preschoolers selectively infer history when explaining outcomes and infer past events that could have plausibly happened. In Experiment 1, thirty-three 3-year-olds and thirty-six 4-year-olds explained why a character owns or likes certain objects. In Experiment 2, thirty-four 4-year-olds and thirty-six 5-year-olds explained why a character either owns or is using the objects. Children aged 4 and 5 years, but not 3 years, inferred history when explaining ownership, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…However, rather than showing sensitivity to creation itself, participants could also have based their judgments on other factors that typically cooccur with creation, such as labor on the object, and time and effort invested in it. Similar issues arise for investigations suggesting that preschool-aged children judge that creation establishes ownership (Nancekivell & Friedman, 2014;Rochat et al, 2014). For instance, Rochat and colleagues found that five-year-olds from seven different cultures attributed ownership of an object to the agent who created it.…”
Section: Existing Findingsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, rather than showing sensitivity to creation itself, participants could also have based their judgments on other factors that typically cooccur with creation, such as labor on the object, and time and effort invested in it. Similar issues arise for investigations suggesting that preschool-aged children judge that creation establishes ownership (Nancekivell & Friedman, 2014;Rochat et al, 2014). For instance, Rochat and colleagues found that five-year-olds from seven different cultures attributed ownership of an object to the agent who created it.…”
Section: Existing Findingsmentioning
confidence: 78%
“…Crucially, the agent acted without directly contacting the target-instead the agent threw some thing at it. For example, in some scenarios the agent threw a rock at a can, crushing 1 This claim is also supported by developmental studies show that children consider objects history in their ownership judgments (e.g., Friedman, Van de Vondervoort, Defeyter, & Neary, 2013;Gelman, Manczak, & Noles, 2012;Gelman, Noles, & Stilwell, 2014;Nancekivell & Friedman, 2014). 2 Our discussion of possession principally concerns the claim that taking physical possession of a non-owned object establishes ownership over it.…”
Section: The Current Approachmentioning
confidence: 95%
“…Thus, people may require experience with museums, economic markets, and/or the signaling value of luxury objects in order to value object features that are neither obvious nor functionally relevant. In contrast, others have proposed that high evaluation of unique objects follows from a foundational, early-emerging belief that objects are imbued with their history (Friedman, Vondervoort, Defeyter, & Neary, 2013; Gelman, 2013; Nancekivell & Friedman, 2014; Newman, in press). On this view, even young children should care about an object's past when evaluating its desirability.…”
mentioning
confidence: 98%
“…From early in development, people track individual agents and objects through space and time (Rich & Bullot, 2014; Xu & Carey, 1996), tag individual people (and sometimes animals and objects) with proper names (Hall, 2009), determine identity and ownership based on an item's historical path (Gelman, Manczak, & Noles, 2012; Gutheil, Gelman, Klein, Michos, & Kelaita, 2008; Nancekivell & Friedman, 2014), and treat owned objects as non-fungible (McEwan, Pesowski, & Friedman, 2016). Additionally, adults in modern Western societies place value (positive or negative) on certain objects because of their past.…”
mentioning
confidence: 99%
“…Specifically, young Western children will attribute ownership to a person that possessed an object first (Friedman & Neary, ), unless they receive conflicting verbal ownership information (Blake, Ganea, & Harris, ). However, children do not just rely on first possession, but also seem to use it as a cue to reconstruct the historical path of possession (Friedman, van de Vondervoort, Defeyter, & Neary, ; Nancekivell & Friedman, ). The first possession heuristic remains relevant beyond childhood, playing a role in adult ownership attributions (Friedman, ; Friedman & Neary, ) and forming the basis of a pivotal legal ruling in North American property law ( Pierson v. Post , ).…”
mentioning
confidence: 99%